Distributed software monitoring and trustworthiness evaluation based on checkpoints - Zhen LI; Jun-feng TIAN; Zhuo CHANG; Xiao-xue MA (Tongxin xuebao)
Traditional software trustworthiness evaluation based on checkpoints and the existing interaction association rules for distributed software were inapplicable to distributed software with complex interactions.According to this problem,an accompanying distributed software monitoring mechanism was used,and three types of checkpoints in nodes and interaction association rules were introduced for complex interaction scene.The trustworthiness of the node instance was evaluated based on checkpoint structure tree by dividing nodes into several modules,and then the trustworthiness of distributed soft-ware was evaluated based on nodes.The experimental results showed that the approaches could evaluate the trustworthiness of distributed software instance accurately with small monitoring cost,and could be suitable for infinitely long paths with no state explosion problem for trustworthiness evaluation of distributed software.